3(a-2)=4b+5

Simple and best practice solution for 3(a-2)=4b+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(a-2)=4b+5 equation:


Simplifying
3(a + -2) = 4b + 5

Reorder the terms:
3(-2 + a) = 4b + 5
(-2 * 3 + a * 3) = 4b + 5
(-6 + 3a) = 4b + 5

Reorder the terms:
-6 + 3a = 5 + 4b

Solving
-6 + 3a = 5 + 4b

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 3a = 5 + 6 + 4b

Combine like terms: -6 + 6 = 0
0 + 3a = 5 + 6 + 4b
3a = 5 + 6 + 4b

Combine like terms: 5 + 6 = 11
3a = 11 + 4b

Divide each side by '3'.
a = 3.666666667 + 1.333333333b

Simplifying
a = 3.666666667 + 1.333333333b

See similar equations:

| 3+-3(-2h+6)= | | 104=4(2-4x) | | x+41=70 | | 6[5-8(-4)]+12=x | | 6(-1+x)=-54 | | 891.25=7.5x+4.75y | | 0.80x+0.05(4-x)=0.10(-88) | | 11-3n=9n+2 | | 157=113-u | | 2(x+19)=x+29 | | 4+4x=x | | -9t+-7(-6+-10)= | | 2(x+9)=x+29 | | y-47=-41 | | x-40=30 | | 22=9n-(-4) | | 6(n-4)=-54 | | 4(m-2)=1 | | 13=6+6 | | log[5]3+log[5]t+log[5](t+4)=log[5]63 | | -2(10x-1)=-48-10x | | 2(x+2)=3x-8 | | 16-7x=-61 | | 10m+9n+4m= | | -4+6(-6+10h)-4h= | | 1.8d+3=2(.9d-1.5) | | A(x)=2x+8x+14 | | 3m+7=7m+6 | | -12+5k=15-45 | | (9x-6)+(3x+8)= | | 7(2+9g)= | | 7.50x+4.75x=891.25 |

Equations solver categories